Mercury accumulation in freshwater and marine fish from the wild and from aquaculture ponds. (December 2019) - Zupo, Valerio; Graber, Gunnar; Kamel, Samar; Plichta, Veronika; Granitzer, Sebastian; Gundacker, Claudia; Wittmann, Karl J.
Abstract: We analysed the total mercury (Hg) accumulation in bodies and gut contents of 13 species of marine wild fish, 7 species of wild freshwater fish and 4 species of farmed fish. In addition, metal concentrations were recorded in water, sediment, fish prey and fodder materials, to track the dynamics of bio-accumulation. Cultured freshwater fish were collected at four Austrian farms and compared with samples obtained from markets. Wild marine fish were collected at Santa Croce bank, in Italy (Mediterranean Sea). Metal accumulation varied with sampling site, species, and age (or weight) of fish. Wild marine fish exhibited higher levels than wild freshwater fish, which in turn had higher Hg levels than cultured freshwater fish. Mercury increased according to trophic levels of consumers. Total Hg contents in muscle of cultured and wild freshwater fish sampled in 2006–2008 did not exceed legal nutritional limits. Similarly, in market samples of trout and carp collected in 2019, we found low or undetectable concentrations of total Hg in muscle tissue. In contrast, some marine fish (both market samples and some species from coastal waters) exceeded the legal limits. Environmental contamination, food webs and biological factors are the main causes of Hg accumulation in fish. Our results reflect the actual differences between specific European sites and should not be generalized. However, they support the generally increasing demand for monitoring mercury pollution in view of its impact on human health and its value as an indicator of ecosystem contamination. Graphical abstract: Image 10 Highlights: High mercury levels were found in marine compared with freshwater European fish. Mercury levels in trout and carp were not significantly correlated with abiotic parameters. Cultured carp showed average mercury levels of 11 μg kg −1 in gut content vs. 39 μg kg −1 in musculature. Young trout (0–11 months) exhibited significantly higher mercury levels than older ones. . Fish living close to the substratum and the benthic sediments contained higher mercury levels. . . Abstract : High mercury levels were found in marine compared with freshwater European fish.